Diversification and Expression of the PIN, AUX/LAX, and ABCB Families of Putative Auxin Transporters in Populus - Carraro, Nicola; Tisdale-Orr, Tracy E.; Clouse, Ronald M.; Knöller, Anne S.; Spicer, Rachel (Frontiers in Plant Science, 2012)
Intercellular transport of the plant hormone auxin is mediated by three families of membrane-bound protein carriers, with the PIN and ABCB families coding primarily for efflux proteins and the AUX/LAX family coding for influx proteins. In the last decade our understanding of gene and protein function for these transporters in Arabidopsis has expanded rapidly but very little is known about their role in woody plant development. Here we present a comprehensive account of all three families in the model woody species Populus, including chromosome distribution, protein structure, quantitative gene expression, and evolutionary relationships. The PIN and AUX/LAX gene families in Populus comprise 16 and 8 members respectively and show evidence for the retention of paralogs following a relatively recent whole genome duplication. There is also differential expression across tissues within many gene pairs. The ABCB family is previously undescribed in Populus and includes 20 members, showing a much deeper evolutionary history, including both tandem and whole genome duplication as well as probable gene loss. A striking number of these transporters are expressed in developing Populus stems and we suggest that evolutionary and structural relationships with known auxin transporters in Arabidopsis can point toward candidate genes for further study in Populus. This is especially important for the ABCBs, which is a large family and includes members in Arabidopsis that are able to transport other substrates in addition to auxin. Protein modeling, sequence alignment and expression data all point to ABCB1.1 as a likely auxin transport protein in Populus. Given that basipetal auxin flow through the cambial zone shapes the development of woody stems, it is important that we identify the full complement of genes involved in this process. This work should lay the foundation for studies targeting specific proteins for functional characterization and in situ localization.